Social anxiety disorder co-morbid with schizophrenia: a cross-sectional study from India - Bipeta, Rajshekhar; SRR Yerramilli, Srinivasa; Lakhan, Ram; A Khan, Majeed (International Journal of Medical Research and Review, 2016)
Introduction: The co-morbidity of various psychiatric disorders with schizophrenia (SZ) is increasingly being recognized, with anxiety disorders (ADs) being no exception. Among the various ADs, the co morbidity of social anxiety disorder (SAD) and SZ is not well studied. We hypothesized that the prevalence of SAD in SZ is high. Objective: We aimed to study the prevalence of SAD in patients with SZ, and to determine the associated socio-demographic and clinical correlates. Materials and methods: This was an outpatient study on consecutively sampled 64 International Diagnostic Criteria (ICD-10) diagnosed treatment-naive SZ patients, who were rated on the Positive and Negative Syndrome Scale (PANSS), the Social Interaction Anxiety Scale (SIAS), the WHO-5 Well-Being Index (WHO-5) and the Global Assessment of Functioning Scale (GAF). Results: The prevalence of SAD in or sample of SZ patients was 26.56%. Compared to the SZ without SAD group, the SZ with SAD group had a lower quality of life (QoL) and GAF scores, but, no significant difference in the PANSS ratings. Conclusions: The SAD is highly co morbid with SZ, and appears to be independent of psychosis, and is associated with lower QoL and psychosocial functioning. Future follow-up studies should evaluate whether this SAD co-morbidity has any impact on the treatment outcome of SZ.